The impact of the SARS-COV-2 pandemic on maternal mortality in a South African Metropole (2020-21) - Hunter, Mehreen Bhorat (Department of Public Health and Family Medicine, 2025)
Background: During the COVID-19 pandemic there was a notable increase in maternal deaths across South Africa. Pre-pandemic, the Western Cape Province had made significant strides towards reducing maternal mortality. However, this progress was reversed in the pandemic period despite a relative protection of maternal care services. The biological impact of SARS-CoV-2 may not be the sole reason for the increase in mortality. Therefore, we aimed to evaluate the relative change in the maternal death rate for non-SARS-CoV-2-related deaths intra-pandemic versus pre-pandemic in 2019. Methods: We conducted a retrospective cohort study involving all pregnant women with a pregnancy outcome enumerated in the Provincial Health Data Centre, in the Metro-West region of Cape Town from 1 January 2019 – 31 January 2022. Cause of in- facility maternal death and relationship to SARS-CoV-2 infection was determined by folder review. We used Interrupted Time Series (ITS) analysis to assess the impact of the pandemic period on non-SARS-CoV-2 causes of maternal mortality. Maternal characteristics reviewed included HIV status and the proportion of maternal deaths occurring in persons living with HIV were also explored. Results: Over 98 000 women were included with 68 deaths reviewed. The ITS model (p =0.01) revealed that the pandemic was associated with a step increase of 3.12 (-1.66;7.9) in maternal mortality rate for non-SARS-CoV-2 related deaths following the start of the pandemic. This impact was sustained with an attenuation in the maternal mortality rate reduction over time from -0.56 pre-pandemic to -0.12 intra-pandemic. Folder review of deaths revealed an increase in opportunistic infections as a cause of death relative to pre-pandemic. Conclusion: Whilst maternal healthcare services were largely protected from service disruptions during the COVID-19 pandemic, there was a reversal of some of the progress made in reducing non-SARS-CoV-2 maternal deaths in prior years. An increase in opportunistic infections and an attenuation of the decline in maternal death rate suggest that optimising maternal health requires the well-functioning of the entire healthcare ecosystem. The indirect impact of health threats, and our responses thereto, need to be strongly considered in future management strategies